A video-based approach to promote safe driving among foreign visitors to Japan. (October 2019) - Yoh, Kento; Uchiyama, Chiemi; Hung, Pai-Hsien; Doi, Kenji
Abstract: Recently, the demand for car rentals has been increasing at tourist destinations in Japan due to their convenience and the high degree of freedom they offer. On the other hand, there is a problem of a dramatic rise in the number of traffic accidents involving drivers from countries with different traffic customs and cultures from Japan. In order to examine measures to reduce the traffic accident risk of foreign drivers visiting Japan, an animation video to promote safe driving was created and its educational effects were tested in this article. First, through a driving survey of foreigners and a review of preceding studies, we identified information on Priority, Speed, and Comprehension (PSC) that must be learned by foreign visitors to reduce their accident risk. Next, drawing from the technique of branded contents in order to enhance the effects of educational videos, we created a short video that conveys the PSC philosophy that should be understood for safe driving in Japan. We then tested the educational effects of the video by conducting a survey of Taiwanese people. The results show that strengthening the video's appeal leads to improvements in educational effects and therefore safety awareness. We also realized that the effect was particularly significant among young people in their twenties. Lastly, the rent-a-car businesses evaluated the videos and basing on their input, we summarized effective ways for foreign rent-a-car users visiting Japan to use the video. Highlights: Propose a series of measures promoting safe driving among foreigners. Identify the information that must be learned by foreign visitors coming to Japan. Create educational animation videos adopting the branded content method. Examine the safety awareness impact of the animation video.